Parking Tax Revenue and Management at Manado City Regional Revenue Agency - Umboh, Gabriela Yuliana; Kandou, Selpius R.; Kairupan, Sisca B. (Technium Social Sciences Journal, 2024)
This research aims to 1) Analyze the strategy of the Regional Revenue Agency (Bapenda) in managing Parking Tax to increase Original Regional Income in Manado City; 2) Analyze the factors that support and hinder the Regional Revenue Agency (Bapenda) in managing Parking Tax to increase Original Regional Income in Manado City. The research method used is a qualitative research method with data analysis techniques using SWOT analysis. The research results show that 1) Based on the results of the SWOT analysis, the Manado City Regional Revenue Agency (Bapenda) has internal strengths and opportunities, so that its strengths and opportunities can be an advantage for the Manado City Regional Revenue Agency (Bapenda) in increasing its Original Regional Income (PAD). ) through parking tax. There are 4 (four) recommended strategies, namely: a) Aggressive in implementing parking tax sanctions and fines, b) Aggressive in improving parking tax services, c) Aggressive in improving parking tax communication and education, and d) Aggressive in increasing parking tax supervision; 2) Supporting factors: (a) Availability of legal umbrella law governing parking tax management, (b) There are sanctions and fines for parking tax objects that are in arrears, late and do not pay taxes, (c) Availability of personnel or officers who available to collect tax payments, (d) Availability of a joint task force team tasked with carrying out supervision and raids, which supports the implementation of parking tax management policies, (e) Improved services, through an online tax payment and reporting system; 3) Inhibiting factors: (a) Low discipline, compliance of parking taxpayers to pay taxes, (b) Low honesty, awareness of parking taxpayers manipulating the amount of income turnover so that tax payments are low, (c) Limited quantity of human resources working and ineffectiveness of the joint task force in carrying out its main duties (d) Implementation of administrative sanctions such as fines, closure and sealing for tax objects that are late, in arrears or even do not pay parking tax, are less effectively implemented, (e) Lack of supporting facilities such as the absence of operational vehicles and limited facilities services such as computers, laptops and printers; (f) External conditions that are less supportive, after the outbreak of the Virus-19 pandemic and the entry of new normal conditions.